Phythochemical Screening and Antimicrobial Activity of Sub Fractions Asam Kandis (Garcinia diocia Blume) - Puji Ardiningsih,Sumarni,Risa Nofiani and Afghani Jayuska (Journal of Applied Pharmaceutical Science)
Fruit flesh of asam kandis Garcinia diocia Blume has been used people in Kalimantan Barat to preserve fresh fish. One of compounds which is probably responsible as a preservative agent is antimicrobial compounds. In this research, flesh fruit of asam kandis was extracted using methanol as a solvent. Furthermore, the crude extract was partitioned using various solvent such as n-hexane and ethyl acetate. On the basis of antimicrobial activity, methanolic and ethyl acetate fractions can inhibit growth of tested microorganisms. The best antimicrobial fraction was showed by ethyl acetate fraction due to inhibit all of tested microorganism but sub fraction E4 can only inhibit Candida albicans which are possibly responsible for antimicrobial activity were categorized as flavonoid.
Keywords: Phytochemical screening,antimicrobial activity,disc diffusion,Garcinia diocia Blume.